Direct synthesis of vertical graphene nanowalls on glass substrate for thermal management. (27th June 2018) - Zhang, Nan; Li, Jiurong; Liu, Zhiduo; Yang, Siwei; Xu, Anli; Chen, Da; Guo, Qinglei; Wang, Gang
Abstract: Vertical few layered graphene (VG) nanoflakes were directly synthesized on traditional glass substrate by the plasma-assisted chemical vapor deposition, where the extremely low growing temperature (<560 °C) and short time (<30 min) were involved. The VG microstructure could be well-controlled by tuning the plasma power, growth time and growth temperature. Raman, TEM, and SEM were used to determine the quality and single size of the VG. Because of the unique three-dimensional structure with high surface area, the VG network can provide superior thermal management capabilities, which has been demonstrated by the scalable frost removal. We believed that this hybrid system consisting of vertical graphene nanowalls and glass substrates has great potentials for future transparent 'green-warmth' constructions.